(untitled) (Brazilian Journal of Radiation Sciences, 2023)
The objective of this paper was the radiometric survey at the Materials Engineering Laboratory of the Military Institute of Engineering, in Rio de Janeiro, Brazil. Properties of materials are analyzed in this laboratory using X-rays machines. For the development of that work, two scintillator detectors were used with their associated electronics. Detector “A” has NaI(Tl) as scintillator material and detector “B” has CeBr3. In addition to verifying whether the measured dose rate is in accordance with that provided by the CNEN standard, a comparison was made between the efficiencies of these radiation detection equipment.